Microstructural evolution and grain refinement in a Cu-Zr alloy processed by high-pressure torsion - Wongsa-Ngam, Jittraporn; Langdon, Terence G. (My University, 2014)
A copper alloy, Cu-0.1% Zr, was processed at room temperature by high-pressure torsion (HPT) in order to evaluate the microstructural evolution and grain refinement mechanism. Transmission electron microscopy (TEM) and electron backscatter diffraction (EBSD) techniques were employed to measure the grain morphology, grain size distributions and the distribution of the misorientation angles. The results demonstrate that this processing procedure has a potential for producing an ultrafine-grain structure containing reasonably equiaxed grain with high-angle boundary misorientations. The grain refinement mechanism is primarily governed by dislocation activities. © (2014) Trans Tech Publications, Switzerland.
Keywords: Copper alloy; Grain refinement; High-pressure torsion; Microstructure